An emerging role for adenosine and its receptors in bone homeostasis - Evans, Bronwen; Ham, Jack (Frontiers in Endocrinology, 2012)
Bone is continually being remodelled and defects in the processes involved lead to bone diseases. Many regulatory factors are known to influence remodelling but other mechanisms, hitherto unknown, may also be involved. Importantly, our understanding of these currently unknown mechanisms may lead to important new therapies for bone disease. It is accepted that purinergic signalling is involved in bone, and our knowledge of this area has increased significantly over the last fifteen years, although most of the published work has studied the role of ATP and other signalling molecules via the P2 family of purinergic receptors. During the last few years, however, there has been increased interest within the bone field in the role of P1 receptors where adenosine is the primary signalling molecule. This review will bring together the current information available in relation to this expanding area of research.